2012
DOI: 10.4319/lo.2012.57.6.1846
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and fate of microphytobenthos carbon in subtropical shallow subtidal sands: A 13C‐labeling study

Abstract: Microphytobenthos (MPB) in photic sediments are highly productive but the fate of this production remains uncertain. Over 33 d, tracing of 13 C from added bicarbonate in subtropical shallow subtidal sand showed rapid transfer of MPB-derived carbon to deeper sediment; below 2 cm (31% within 60 h) and 5 cm (18%). Despite their high turnover (5.5 d) and only representing , 8% of sediment organic carbon, MPB represented up to 35% of the 13 C retained in sediments, demonstrating substantial carbon recycling. Carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(106 citation statements)
references
References 43 publications
9
95
2
Order By: Relevance
“…It is only on the timescale of ocean bottom-water renewal (100-1000 years) that nutrients regenerated by benthic organisms may impact primary producers in the sunlit upper part of the ocean (Soetaert et al, 2000). This is obviously different for sediments in the photic zone that make up about one-third of the coastal ocean (Gattuso et al, 1996) because animals can directly graze and consume the benthic primary producers at the sediment surface Evrard et al, 2010Evrard et al, , 2012Oakes et al, 2012;Fig. 5).…”
Section: Animals and Carbon Supply To Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is only on the timescale of ocean bottom-water renewal (100-1000 years) that nutrients regenerated by benthic organisms may impact primary producers in the sunlit upper part of the ocean (Soetaert et al, 2000). This is obviously different for sediments in the photic zone that make up about one-third of the coastal ocean (Gattuso et al, 1996) because animals can directly graze and consume the benthic primary producers at the sediment surface Evrard et al, 2010Evrard et al, , 2012Oakes et al, 2012;Fig. 5).…”
Section: Animals and Carbon Supply To Sedimentsmentioning
confidence: 99%
“…Various types of experimental evidence have shown that carbon flow through the living compartment is much higher than through the nonliving sediment organic matter pool. Short-term in situ experiments using 13 C-and/or 15 N-labeled organic matter (e.g., phytodetritus) revealed rapid incorporation of 13 C / 15 N in physically separated organisms (macro-and meiofauna and foraminifera) and microbes, the latter via incorporation of tracers in biomarkers specific for certain microbial groups Boschker and Middelburg, 2002;Veuger et al, 2007;Oakes et al, 2012;Woulds et al, 2007Woulds et al, , 2016 Similarly, ammonium isotope dilution studies have shown that net ammonification (ammonium release) is only a fraction of the total ammonium regeneration because a substantial part of the ammonium liberated is re-assimilated by the microbial community (Blackburn and Henriksen, 1983). Clearly the microbes and animals living in sediment assimilate carbon and synthesize new biomass (Veuger et al, 2012).…”
Section: Secondary Production and The Formation Of Molecularly Uncharmentioning
confidence: 99%
“…The in situ approach has been successfully applied to elucidate food webs in lakes (Pace et al, 2004(Pace et al, , 2007, streams (Hall and Meyer, 1998), estuaries , tidal marshes (Gribsholt et al, 2005(Gribsholt et al, , 2009), tidal flats Rossi et al, 2009), coral reefs (de Goeij et al, 2013 and deep-sea sediments (Blair et al, 1996). Heavy isotope-enriched materials have also been added in situ to benthic chambers in coastal (Oakes et al, 2010(Oakes et al, , 2012 and deep-sea sediments (Moodley et al, 2002;Witte et al, 2003) and to cores implemented at the seafloor (Nomaki et al, 2011).…”
Section: Stable Isotopes As Deliberate Tracers In Food-web Studiesmentioning
confidence: 99%
“…13 C-bicarbonate stable isotope probing (SIP) has demonstrated differential labeling of constituent sugars in diatom carbohydrate fractions from MPB (Bellinger et al 2009;Oakes et al 2010); with subsequent incorporation of 13 C-labeled carbon into the phospholipid fatty acids (PLFAs) of various bacterial groups Bellinger et al 2009;Gihring et al 2009). Though bacterial utilization may result in significant mineralization of diatom EPS to dissolved inorganic carbon (Oakes et al 2010(Oakes et al , 2012, a proportion of this carbon is incorporated into bacterial biomass, e.g., peptidoglycans, where it can contribute to the longer term retention of organic carbon within sediments (Veuger et al 2006).…”
mentioning
confidence: 99%